(untitled) (OCEM Journal of Management, Technology & Social Sciences, 2026)
Food transcends sustenance, reflecting memory, migration, identity, and cultural expression. Dumplings exemplify culinary diversity, with Mo:Mo from Nepal being a key focus. This study delves into Mo: Mo’s historical roots, cultural significance, wellness aspects, and global presence, advocating for its recognition as Nepal’s national dish and a candidate for UNESCO Intangible Cultural Heritage, highlighting its importance as both a culinary and cultural symbol. This research is based on a narrative literature review tracing the evolution of dumplings from Zhang Zhongjing’s medicinal jiaozi in ancient China, through Tibetan Mog, to contemporary Nepali Mo:Mo. This historical trajectory highlights the adaptation of dumpling culture across diverse geographical, climatic, and socio-cultural environments, illustrating processes of culinary transformation and localisation. The findings suggest that Mo:Mo has transcended its identity as a simple food item to become a powerful marker of social cohesion, cultural identity, and national pride in Nepal. Its influence extends beyond the Kathmandu Valley, with Mo:Mo now widely consumed by Nepali diaspora communities in cities such as Delhi, New York, and London, where it serves as both a culinary link to home and a symbol of cultural continuity. The study highlights the broader implications of Mo:Mo’s cultural “DNA” for tourism development, hospitality industries, and cultural heritage institutions. It also emphasises Mo:Mo’s growing global presence, suggesting the need for stronger cultural policy frameworks to support the preservation of food heritage and promote its recognition in international cultural and tourism sectors.